Long‐distance Friends and Collective Action in Fisheries Management - Kristopher M. Smith; Anne C. Pisor; Bertha Aron; Kasambo Bernard; Paschal Fimbo; Haji Machano; Rose Kimesera; Jason Rubens; Lorna Slade; Jumanne Sobo; Ali Thani; Monique Borgerhoff Mulder (Conservation Letters)
ABSTRACT Much received wisdom in the conservation literature is that individual connections across community boundaries undercut natural resource management. However, when multiple communities access the same resource, these long‐distance relationships could generate interdependence and trust to motivate engagement in collective action to manage the resource. To test this, we interviewed 1317 people in 28 fishing villages in Tanzania about their participation in managing open‐access fisheries and their social relationships in each village accessing the fishery. People with more friends in other villages trusted more people in those villages and were more likely to participate in collective action to manage the shared fishery, such as reporting others for destructive fishing practices. These results show that long‐distance relationships may be a useful foundation upon which to build conservation efforts that cross community boundaries and bolster sustainable resource use.